(untitled) (Edad Media. Revista de Historia, 2025)
The Alentejo symbolically became the starting point for King Afonso V’s entry onto Castilian soil in 1475, with around 20,000 men concentrated in Arronches, in what would become known as the Toro campaign. While this was happening, the region’s fortresses were abandoned to their fate and the territory at the mercy of predatory attacks from the neighbouring kingdom. In this article we analyse the tools that the Portuguese king used to try to balance the forces, in a dangerous and risky but necessary game that sought to combine strategy in the field of military operations with the political instability that was taking place in Castilian Extremadura.